The prevalence of primary Sjogren's syndrome in a multiple sclerosis population. - Noseworthy, J; Bass, B; Vandervoort, M; Ebers, G; Rice, G; Weinshenker, BG; McLay, C; Bell, D (1989)
A central nervous system illness closely resembling multiple sclerosis has been described in patients with primary Sjögren's syndrome. From these reports, the estimated prevalence of this syndrome could be similar to that of multiple sclerosis in a high-frequency area. We evaluated 192 consecutive patients in our multiple sclerosis clinic to determine if such cases had gone unrecognized. We did not find any patients with clinical or serological evidence of primary Sjögren's syndrome. We conclude that it is rare for neurological manifestations of Sjögren's syndrome to mimic multiple sclerosis in our population.